Embolia pulmonar: relação entre escores tomográficos e prognósticos clínicos - Thiago Horta Soares (2011)
Background: Pulmonary embolism (PE) is a serious and potentially fatal disorder. Risk stratification of death in PE allows identification of low risk patients who may be treated as outpatient or discharged early and also prevents deaths by early medical intervention in high risk groups. Methods: We evaluated 126 patients with objectively confirmed PE by a multidetector computed tomographic pulmonary angiography from a single center from January 2008 to January 2010. Variables used to calculate the Pulmonary Severity Embolism Index (PESI), the right to left ventricle diameter (RV/LV) ratio and the vascular obstruction index (VOI) were extracted from electronic hospital records and image database. Results: a total of 6/96 patients (6.3%) died during follow-up. There was an association between PESI and mortality (2 p < 0.001). PESI class I-II had a 100% negative predictive value of death in 90 days. No association was found between the RV/LV ratio, the VOI and mortality (2 p > 0.05). Also, no association was found between the RV/LV ratio and the VOI and PESI (2 p > 0.05). Conclusions: PESI is an accurate tool in PE prognostic stratification. It discriminates safely patients with low and high risk of death. We were unable to demonstrate association between images scores and mortality.